2021
DOI: 10.2196/31844
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Virtual Reality Treatment on Prefrontal Cortex Activity in Patients With Social Anxiety Disorder: Participatory and Interactive Virtual Reality Treatment Study

Abstract: Background Attempts to use virtual reality (VR) as a treatment for various psychiatric disorders have been made recently, and many researchers have identified the effects of VR in psychiatric disorders. Studies have reported that VR therapy is effective in social anxiety disorder (SAD). However, there is no prior study on the neural correlates of VR therapy in patients with SAD. Objective The aim of this study is to find the neural correlates of VR ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Further findings were that outcome expectancy (Price & Anderson, 2012), mindfulness (Burton, Schmertz, Price, Masuda, & Anderson, 2013), and social costs, self-focused attention and self-efficacy (Kampmann, Emmelkamp, & Morina, 2019) influence the effect of exposure therapy regardless of the type of exposure and that the working alliance between therapist and patient similarly increases during treatment in both VRET and exposure group therapy (Ngai, Tully, & Anderson, 2015). Moreover, regarding neural correlates, changes in brain activity in the prefrontal and orbitofrontal cortex (Lee, Choi, Jung, Hur, & Cho, 2021), as well as changes in activation in various brain areas in a selfreferential stimuli processing task (Hur et al, 2021) were found after six sessions of VRET with additional CBT elements. Additionally, fewer dropouts from individualized VRET compared to exposure group therapy were found in an RCT by Johnson, Price, Mehta, and Anderson (2014).…”
Section: Therapy Studiesmentioning
confidence: 98%
“…Further findings were that outcome expectancy (Price & Anderson, 2012), mindfulness (Burton, Schmertz, Price, Masuda, & Anderson, 2013), and social costs, self-focused attention and self-efficacy (Kampmann, Emmelkamp, & Morina, 2019) influence the effect of exposure therapy regardless of the type of exposure and that the working alliance between therapist and patient similarly increases during treatment in both VRET and exposure group therapy (Ngai, Tully, & Anderson, 2015). Moreover, regarding neural correlates, changes in brain activity in the prefrontal and orbitofrontal cortex (Lee, Choi, Jung, Hur, & Cho, 2021), as well as changes in activation in various brain areas in a selfreferential stimuli processing task (Hur et al, 2021) were found after six sessions of VRET with additional CBT elements. Additionally, fewer dropouts from individualized VRET compared to exposure group therapy were found in an RCT by Johnson, Price, Mehta, and Anderson (2014).…”
Section: Therapy Studiesmentioning
confidence: 98%
“…There is a dearth of research pertaining to comparative studies on self-reported scores and neural correlates during VRET in treating SAD. A recent VRET study showed that self-rating scores were consistent with neural correlates in SAD ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies reveal that the difference between the brain activity of the prefrontal cortex of SAD and control groups at baseline is statistically significant ( Pittig et al, 2018 ; Lee et al, 2021 ; Kredlow et al, 2022 ). There is a dearth of research pertaining to comparative studies on self-reported scores and neural correlates during VRET in treating SAD.…”
Section: Discussionmentioning
confidence: 99%
“…And by June 2022, Sony Entertainment Interactive released its second-generation VR device, which consists of a headset and two controllers that fit into the palm of the hand. It will need to run with the latest PlayStation 5th-generation console when in use, and in addition to the classic Half-Life alyx and Rhythm Lightsaber being playable, it will be possible to use it in 2023 to play the massive VR DLC for Resident Evil 8 and Horizon West of Extinction [9][10][11]. In the film Top Gun, released in 2018 during this period, the famous director Spielberg used cinematography to portray the heavenly world of virtual reality, making this technological frontier deep in the minds of the general public [12].…”
Section: The Composition and Interaction Of Vrmentioning
confidence: 99%